Quantitative Determination of Pitavastatin in Tablets Using FTIR and RP-HPLC Analysis: A Comparative Study - AlKadi, Hourieh; Alzier, Ali; Mando, Huda; Mando, Zaynab; Darwicha, Jamal A. N.; Allaf, Abdul W. (Infectious Disorders - Drug Targets, 2022)
Background: Fourier Transform Infrared (FTIR) spectroscopy and reverse phase highperformance liquid chromatography, RP-HPLC analysis have been used for the quantitative determination of local l commercially available Pitavastatin products. Methods: The FTIR method of analysis is not widely used in pharmaceutical quality control laboratories. This technique is non-destructive, reliable, precise, and efficient, and the samples can be prepared easily. These features emphasized that the FTIR technique can be considered as a potential analytical method for quantitative analysis in pharmaceutical laboratories. Results: It is strongly recommended that FTIR analytical method can be applied simultaneously with RP-HPLC techniques for quality control purposes of drug analysis. Both methods of analysis have shown comparable precision and good repeatability and reproducibility for analysis of Pitavastatin which can be generalized for other pharmaceutical products. Conclusion: In addition, FTIR is not only used for the determination of vibrational modes and structure in the fingerprint region, but it can be also generally applied in quantitative analysis for many pharmaceutical products.
Keywords: quantitative